Is the removal of a central venous catheter always necessary in the context of catheter-related right atrial thrombosis?. Issue 1 (January 2019) - Rossi, Luigi; Libutti, Pasquale; Casucci, Francesco; Lisi, Piero; Teutonico, Annalisa; Basile, Carlo; Lomonte, Carlo
Catheter-related right atrial thrombosis is a severe and life-threatening complication of central venous catheters in both adult and young patients. Catheter-related right atrial thrombosis can occur with any type of central venous catheters, utilized either for hemodialysis or infusion. Up to 30% of patients with central venous catheter are estimated to be affected by catheter-related right atrial thrombosis; however, neither precise epidemiological data nor guidelines regarding medical or surgical treatment are available. This complication seems to be closely associated with positioning of the catheter tip in the atrium, whereas it is unlikely with a tip located within superior vena cava. Herein, we report the case of a patient affected by catheter-related right atrial thrombosis, who showed a quick resolution of thrombosis with a new therapeutic scheme combining loco-regional thrombolytic therapy (urokinase as a locking solution) and systemic anticoagulation therapy (vitamin K antagonists), thus avoiding catheter removal. Neither complications of the combination therapy were reported, nor recurrence of catheter-related right atrial thrombosis occurred. In conclusion, the combination therapy here described was safe, quick and effective, achieving the goal of not removing the catheter.